Feminist space in magical realism: coexistence of magic and feminist tropes in Joanne Harris’ Chocolate and The Lollipop Shoes - Islam, Jessica (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2019.